2018
DOI: 10.1007/s11739-018-1880-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver injury following Garcinia cambogia weight-loss supplementation: case series and literature review

Abstract: Herbal weight-loss supplements are sold as self-medication products, and are often used under the misconception that their natural origin guarantees their safety. Food supplements are not required to provide any benefit/risk profile evaluation before marketing; however, possible risks associated with use of herbal extracts in food supplements are becoming more and more documented in the literature. Some herbs are listed as the leading cause of herb-induced liver injury, with a severe or potentially lethal clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 66 publications
0
68
0
Order By: Relevance
“…Spontaneous reports of suspected AEs to natural health products (including galenic preparations containing herbals) are collected in Italy within the Italian Phytovigilance system coordinated by the National Institute of Health …”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous reports of suspected AEs to natural health products (including galenic preparations containing herbals) are collected in Italy within the Italian Phytovigilance system coordinated by the National Institute of Health …”
Section: Introductionmentioning
confidence: 99%
“…Excessive production of ketone bodies under such conditions may lead to diabetic ketoacidosis 37,38 resulting in drop of pH levels leading to damaging effect on other organs like kidney, liver and muscle in the long run. [39][40][41] As a precaution it should be noted that HCA consumption should not be accompanied with high fat diet in order to prevent side effects like hepatic ketogenesis. 42 Moreover, the increase in glycogen and protein synthesis 17 can result in increased muscle mass in the body or an increase in plasma nitrogen levels (in the form of urea (BUN) or amino acids) depending on the presence or absence of exercise in lifestyle.…”
Section: Resultsmentioning
confidence: 99%
“…143 Furthermore, two review articles that were published in the same year reviewed and discussed an array of G. cambogia induced liver injury. 144,145 A clinical investigation of a 82-year-old male, after the consumption of G. cambogia, revealed that the patient had fats deposited around the pancreas that was well-matched with acute pancreatitis. 146 Moreover, a report suggested that a 35-year-old female consumed G. cambogia and soon developed nausea, headache, dizziness and swelling of the eyes.…”
Section: Resultsmentioning
confidence: 99%